Phylogenetic and morphological analyses of species of Marasmius sect. Marasmius from the Atlantic Rainforest, Brazil - Oliveira, Jadson José Souza de; Moncalvo, Jean Marc; Margaritescu, Simona; Capelari, Marina (Plant Systematics and Evolution, 2020)
Marasmius is a genus of mushroom-forming fungi known to harbor a large diversity of species and morphological structures. To date, sections Globulares, Leveilleani, Marasmius, Neosessiles, and Sicci (traditional view) are confirmed in Marasmius s.s. This study focused on the taxa of Marasmius sect. Marasmius, with 18 species from the Atlantic Rainforest of Southeastern Brazil herein included in morphological and phylogenetic analyses based on nrITS data, along with species of the section from various tropical and temperate areas of the World. Seven new species are described: Marasmius alienigenus sp. nov., M. avellaneus sp. nov., M. gracilis sp. nov., M. longibasidiatus sp. nov., M. subputtemansii sp. nov., M. subvigintifolius sp. nov., and M. ypyrangensis sp. nov. Additionally, Marasmius sect. Marasmius subsect. Horriduli is herein emended based on evidences from phylogenetic and morphological analyses. Subsection Horriduli circumscribes foliicolous species producing basidiomata containing Chrysochaetes-type elements in the pileipellis and lamellar edge. This prompts the perspective of a pluralistic view in how characterizing structures of the pileipellis and cheilocystidia to replace the paradigmatic dichotomy Rotalis-Siccus in classification. © 2020, Springer-Verlag GmbH Austria, part of Springer Nature.